Insight into selectivity: uptake studies of radionuclides 90Sr2+, 137Cs+, and 233UO22+ with bis-amidoxime polymers. Issue 15 (28th March 2018) - Piechowicz, Marek; Chiarizia, R.; Soderholm, L.
Abstract : Density functional theory and separation experiments combine to demonstrate the selectivity of bis-amidoxime polymer for uranyl extraction from aqueous solution. Abstract : Uptake characteristics of a bis-amidoximated polymer are presented for 90 Sr 2+, 137 Cs +, and 233 UO2 2+ to assess rational ligand design and polymer engineering efforts applied to selective uranium extraction. Functionalized with the bis-amidoxime diaryl ether ligand at a loading of 1.98 mmol per gram of polymer, the polymer was found to sorb uranium from a pH 6 solution with a separation factor ( α ) over cesium of 1.2 × 10 3 . Strontium uptake was negligible throughout the pH range studied whereas cesium uptake averaged <30%. Moreover, at near neutral pH, the sorbent was able to purify water to below the United States' set maximum contaminant level for uranium, decreasing the U concentration from 330 ppb to below 3 ppb in 30 minutes. Density functional theory (DFT) calculations, used to probe the nature of the metal-bis-amidoxime interaction, help inform the empirically realized uptake selectivity.